On prosperity and posterity: the need for fiscal discipline in a monetary union - Carsten Detken; Vítor Gaspar; Bernhard Winkler (European Central Bank (ECB), 2004)
We show how in a Blanchard-Yaari, overlapping generations framework, perfect substitutability of government bonds in Monetary Union tempts governments to exploit the enlarged common pool of savings. In Nash equilibrium all governments increase their bond financed transfers to current generations (prosperity effect) at the expense of future generations (posterity effect). The resulting deficit bias occurs even if one assumes that before Monetary Union countries had eliminated their deficit bias by designing appropriate domestic institutions. The paper provides a rationale for an increased focus on fiscal discipline in Monetary Union, without the need to assume imperfect credibility of existing Treaty provisions or to refer to extreme situations involving sovereign default. We draw on existing empirical evidence to argue that the degree of government bond substitutability within the European Monetary Union is an order of magnitude larger than in the global economy.
Keywords: D62; E61; E63; 330; bond market integration; common pool; European Monetary Union; fiscal discipline; fiscal rules; fiscal spillover effects; overlapping generations